An Encapsulation‐Based Sodium Storage via Zn‐Single‐Atom Implanted Carbon Nanotubes. Issue 31 (5th July 2022) - Li, Xin; Ye, Weibin; Xu, Pan; Huang, Haihong; Fan, Jingmin; Yuan, Ruming; Zheng, Ming‐Sen; Wang, Ming‐Sheng; Dong, Quanfeng
Abstract: The properties of high theoretical capacity, low cost, and large potential of metallic sodium (Na) has strongly promoted the development of rechargeable sodium‐based batteries. However, the issues of infinite volume variation, unstable solid electrolyte interphase (SEI), and dendritic sodium causes a rapid decline in performance and notorious safety hazards. Herein, a highly reversible encapsulation‐based sodium storage by designing a functional hollow carbon nanotube with Zn single atom sites embedded in the carbon shell (ZnSA ‐HCNT) is achieved. The appropriate tube space can encapsulate bulk sodium inside; the inner enriched ZnSA sites provide abundant sodiophilic sites, which can evidently reduce the nucleation barrier of Na deposition. Moreover, the carbon shell derived from ZIF‐8 provides geometric constraints and excellent ion/electron transport channels for the rapid transfer of Na + due to its pore‐rich shell, which can be revealed by in situ transmission electron microscopy (TEM). As expected, Na@ZnSA ‐HCNT anodes present steady long‐term performance in symmetrical battery (>900 h at 10 mA cm −2 ). Moreover, superior electrochemical performance of Na@ZnSA ‐HCNT||PB full cells can be delivered. This work develops a new strategy based on carbon nanotube encapsulation of metallic sodium, which improves the safety and cycling performance of sodium metal anode. Abstract : Designing a functional encapsulation‐based sodium storage void with abundant pore structure and enriched Zn single atom sites in the inner wall is presented here. Zn single atoms provide abundant selective sodiophilic nucleation sites. Due to the rich pore structure, ZIF‐derived carbon shells can provide geometric constraints and excellent ion/electron transport channels to maintain fast electron/ion contact, benefiting for encapsulating large amounts of metallic sodium.